Can the mechanoreceptional setae of a feeding‐current feeding copepod detect hydrodynamic disturbance induced by entrained free‐floating prey?. Issue 12 (4th October 2021) - Shen, Xinhui; Yao, Xin; Marcos,; Fu, Henry C.
Abstract: Copepods that catch prey using feeding currents beat their cephalic appendages to generate flow entrainment, and detect the presence of nearby prey through the mechanoreceptional setae on the antennules and other appendages. It remains unclear whether the feeding current can be used by the copepod to gain information about its surroundings by sensing when the current is disturbed by nearby particles. In this article, we present a numerical model to address how much the presence of free‐floating prey can alter the feeding current velocity field, and how these prey‐induced disturbances modify setal deformation patterns. We prescribe the beating strokes of the feeding appendages, and quantify the changes in the bending flows across the setae and setal deformations due to the prey entrainment. We find that, first, the seta bends more due to the time‐averaged velocity component of the feeding current, while filtering out the oscillatory component. Second, 100 μ m diameter free‐floating prey do not induce any noticeable change in deformations of the proximal and distal setae unless they are less than 10 or 5.5 prey radii from the antennules, respectively. Larger prey cause bigger flow disturbances than small prey, which are expected to be even harder to detect. Last, if setae are responsive to changes in deformation relative to the deformations in the absence of prey, the distal seta may have long‐ranged sensitivity to assist in detection of prey near the proximal seta, but if setae are responsive to absolute changes in deformation, both setae have very short‐ranged sensitivity.